To solve the equation
\[ x^{10/3} = 27 \cdot x^{1/3}, \]
we start by rewriting \(27\) as \(3^3\):
\[ x^{10/3} = 3^3 \cdot x^{1/3}. \]
Now, we can rearrange the equation:
\[ x^{10/3} - 3^3 \cdot x^{1/3} = 0. \]
Next, we can factor out \(x^{1/3}\):
\[ x^{1/3} \left(x^{10/3 - 1/3} - 27\right) = 0. \]
This simplifies to:
\[ x^{1/3} \left(x^3 - 27\right) = 0. \]
Now, we have two factors that can be set to zero:
- \(x^{1/3} = 0\)
- \(x^3 - 27 = 0\)
From the first factor, \(x^{1/3} = 0\) gives:
\[ x = 0. \]
From the second factor, \(x^3 - 27 = 0\) gives:
\[ x^3 = 27 \implies x = 27^{1/3} = 3. \]
Thus, the solutions for \(x\) are:
\[ \boxed{0} \text{ and } \boxed{3}. \]